Development of an oral vaccine using recombinant viral haemorrhagic septicaemia virus glycoproteins produced in tobacco - Tae Geum Kim; Bong Jo Kang; Sang Ik Park; Tae Jung Kim (Veterinární Medicína, 2019)
The viral haemorrhagic septicaemia virus (VHSV) causes high mortality in many marine and freshwater fish species, resulting in heavy economic losses in fish farming. Previously, cholera toxin B subunit (CTB)-fused recombinant viral haemorrhagic septicaemia virus glycoproteins (rec-VHSV-GPs) have been successfully expressed in tobacco, Nicotiana benthamiana. Here, we evaluated the potential of rec-VHSV-GPs as an oral vaccine against a live viral challenge. After immunisation of mice and fish (olive flounder, Paralichthys olivaceous) with those antigenic proteins in a feed additive form, the antibody titres were increased statistically, especially in the primed groups (P < 0.0001) in both the mouse and fish. After the viral challenge under low water temperature culture conditions (below 18 °C), the immunised fish were protected successfully against the challenge, showing a significantly lower mortality rate (P < 0.05). This result suggests that this plant-based immunisation system could induce an effective immune response. It could be used as a candidate to develop an oral vaccine for fish.